KEKUATAN HUKUM SURAT KETERANGAN AHLI WARIS YANG DIKELUARKAN KEPALA DESA SEBAGAI ALAS HAK DALAM PEMBUATAN AKTA PENGIKATAN JUAL BELI (PJB) OLEH NOTARIS BAGI WNI BUMIPUTERA - LATIFAH HANUM (PREMISE LAW JURNAL, 2016)
Certificate of Heir for native citizens is usually made by the heirs themselves, signed by Village Head, and acknowledged by Subdistrict Head. Besides that, it can also be directly made by Village Head and acknowledged by Subdistrict Head; it contains the names of heirs who have the right to inherit the property. The research used judicial normative and descriptive analytic method. The result of the research shows that Certificate of Heir which is made by the heirs, signed by Village Head, and acknowledged by Subdistrict Head. A Notary is not responsible for a sales contract which uses Certificate of Heir issued by Village Head, and thus it is considered invalid. A Notary is only responsible for the authenticity of a Sales Contract drawn up by him since it is in line with the prevailing legal provisions on Notarial Position as stipulated in UUJN (Notarial Act) No. 30/2004 juncto UUJNNo. 2/2014. Keywords: Certificate of Heir, Village Head, Notary, Native Citizens